Determination of Metabolic Stability Using Cryopreserved Hepatocytes from Rainbow Trout (Oncorhynchus mykiss). Issue 1 (6th August 2015) - Fay, Kellie A.; Nabb, Diane L.; Mingoia, Robert T.; Bischof, Ina; Nichols, John W.; Segner, Helmut; Johanning, Karla; Han, Xing
Abstract: Trout provide a relatively easy source of hepatocytes that can be cryopreserved and used for a range of applications including toxicity testing and determination of intrinsic clearance. Standard protocols for isolating, cryopreserving, and thawing rainbow trout hepatocytes are described, along with procedures for using fresh or cryopreserved hepatocytes to assess metabolic stability of xenobiotics in fish by means of a substrate depletion approach. Variations on these methods, troubleshooting tips, and directions for use of extrapolation factors to express results in terms of in vivo intrinsic clearance are included. These protocols have been developed for rainbow trout, but can be adapted to other fish species with appropriate considerations. © 2015 by John Wiley & Sons, Inc.